DEVELOPMENT OF HYPOTHETICAL LEARNING TRAJECTORY FOR LINEAR EQUATIONS WITH PISA AND SCIENTIFIC APPROACH MODEL CONSIDERATION - Apriyanti, Muda; Suweken, Gede; Suparta, I Nengah (Jurnal Pengajaran MIPA, 2019)
Prediction of how learning might proceed can be used as a basis for designing and achieving successful learning. A Hypothetical Learning Trajectory (HLT) consisted of learning goals, a set of learning activities, and a hypothesized learning process was developed for learning linear equations in which PISA and the scientific approach model also became points of consideration. HLT implementation in three learning schemes suggested the importance of scaffolding in learning linear equations. Sufficient and strategic scaffolding can improve student’s understanding and facilitate the students in overcoming obstacles when learning linear equations.